Piperaceae endémicas del Perú - León, Blanca (2006)
The Piperaceae are represented in Peru by three genera and 830 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly herbs and shrubs. Here we recognize 491 species and 68 varieties as endemics in two genera. Piper is the genus with the largest number of endemic species. This family requires more attention both in its taxonomy and herbaria collection. These endemic taxa are found mainly in Humid Lowland Amazonian Forests, Very Humid Montane Forests and Very Humid Premontane Forests regions, between 100 and 2700 m elevation. We applied IUCN categories and criteria to 209 taxa. Apparently, only nine taxa have been recorded in the Peruvian System of Protected Natural Areas.